Light-induced Hemiplegia, an Atypical Case of Retinal Steal Syndrome. Issue 2 (March 2017) - Kerek, David; Al Kasab, Sami; Antonucci, Michael U.; Turner, Raymond D.; Turan, Tanya N.
Abstract : Atherosclerosis affecting the carotid arteries accounts for up to 20% of ischemic strokes 1. The clinical effects of atherosclerotic occlusive disease vary according to multiple factors, one of which is collateral circulation. In response to a chronic decrease in cerebral perfusion from atherosclerotic occlusion, alternative flow pathways, or collaterals, develop in a variety of patterns. In the setting of carotid occlusion, flow from the Circle of Willis, if complete, often comprises the main cerebral collateral network. In addition, contributions from leptomeningeal and extracranial to intracranial collaterals may develop. In the latter, reversal of flow in the ophthalmic artery can reconstitute to restore supraclinoid internal carotid artery flow. We report a case of the unusual sequela of a collateral flow pattern via the ophthalmic artery that induces a unique retinal steal phenomenon.